Gender Sebagai Pemoderasi Pengaruh Orientasi Tujuan dan Self-Efficacy pada Audit Judgment - Sidhimantra, I Gusti Agung Rama; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2021)
The results of the study of goal orientation and self-efficacy on audit judgment found inconsistencies that are suspected because there are other factors that influence the relationship between the independent variable and the dependent variable. The gender variable as a moderating variable is expected to explain the inconsistency. This study aims to test gender to moderate the effect of goal orientation and self-efficacy on audit judgment. The population of this study were all auditors who worked at public accountant office in the Bali region who were registered in Indonesian Institute of Public Accountant 2020 as many as 110 people. The method of determining the sample is non-probability sampling method with purposive sampling technique, while the method of data collection uses survey method with questionnaire technique. The analysis technique used is moderated regression analysis. The results showed that goal orientation and self-efficacy had a positive effect on audit judgment. Gender strengthens the effect of goal orientation on audit judgment while Gender weakens the effect of self-efficacy on audit judgment. Keywords: Goal Orientation; Self-Efficacy; Gender; Audit Judgment.